Analisis Terhadap Penerapan Keaktivan Belajar Mahasiswa PAK Melalui Metode Tanya Jawab di STT Sabda Agung Surabaya - Melyarmes Hodner Kuanine; Rini Lesta Yanti Harefa; Kristian Edison Yohanis Melkior Afi (IAKN Tarutung, 2023)
One of the teacher's challenges in managing learning in the classroom is when students become passive. This condition requires educators to understand specifically about the characteristics and behavior of students when learning takes place. This study uses a descriptive qualitative method with a literature study approach. This study was conducted to analyze and describe the learning activities of PAK students at STT Sabda Agung, as well as the indicators and factors that influence it. The results of this study can be described as follows. First, students can construct their learning experiences effectively, in addition to educators, teaching materials, and the implementation of learning methods can support the activeness of the teaching and learning process. Second, the learning method applied or used is right on target, thus affecting the level of student participation in the learning process. Third, the method or system used in learning is adjusted to the characteristics of students so that they can know, understand, use and master learning materials. Fourth, the use of the question and answer method as an effort to involve students so that they actively think with questions from the lecturer and between students and in the end it is hoped that the application of this method will bring students success in learning.